Essays in empirical banking - Wang, Weichao (2022)
This thesis serves as my doctoral thesis entitled “Essays in Empirical Banking” that is submitted in partial fulfillment of the requirements for the doctoral degree in administration (finance track) at the Brazilian School of Public and Business Administration (EBAPE) of Getulio Vargas Foundation (FGV) in Rio de Janeiro, Brazil. In this thesis, I include three research chapters in which I study three research questions in the area of empirical banking. First and foremost, I investigate whether labor turnover affects bank risk and performance in commercial lending in the second chapter. Next, I investigate whether the COVID-19 pandemic itself and ensuring government policy interventions jointly affect local credit under the COVID-19 crisis in the third chapter. Last but not least, I investigate whether local personal income taxes affect small business lending in the fourth chapter.